Legal and ethical duties of corporate managers - Jalil, Md. Abdul (2010)
The Companies Act 1965 (Malaysia) provides certain duties to corporate managers which must be followed and complied with. These duties are imposed by law to ensure excellent performance and high productivity in the corporation. These duties also can ensure outstanding project management in the corporation. Those duties are: i) To be honest and speak the truth about the quality of products, ability to perform work etc. at all times; ii) To use reasonable diligence, skill and care; iii) Not to misuse inside information of the corporation; iv) Acting bona fide in the interest of the company; v) Disclosing personal interest in any transaction with the company; vi) Not to make secret profit by using manager position; vii) Avoiding conflict of interest with the company and so on. It is not the only duty of corporate managers to maximize profit for the company but they have other important duties such as corporate social responsibility (CSR) and sustainable development (SD). The objective of the paper is to analyze that if legal and ethical duties are implemented properly in corporations, there is a possibility that the concept of good management and good governance will flourish in corporate business and the productivity in corporate sector will increase.